Method for producing polyacrylonitrile-based polymers with high conversion rate
By reacting acrylonitrile with a radical starter agent and specific comonomer in a liquid medium, the method enhances the conversion of acrylonitrile to polyacrylonitrile polymer, achieving high conversion rates and maintaining carbon fiber properties, thereby reducing waste and costs in the carbon fiber production process.
Patent Information
- Application Number
- JP2021525628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-16
- Filing Date
- 2019-11-15
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2039-11-15
AI Technical Summary
The existing methods for producing polyacrylonitrile (PAN) polymer in the carbon fiber manufacturing process result in low conversion rates of acrylonitrile to PAN polymer, leading to waste and increased costs due to inefficient use of resources and energy, without maintaining the desirable characteristics of the polymer and carbon fiber.
A method involving the reaction of acrylonitrile with a radical starter agent in a liquid medium, in the presence of a specific amount of comonomer and without a chain mobilizer, to produce a polyacrylonitrile polymer, followed by spinning, extension, oxidation, and carbonization processes to form carbon fiber.
This method achieves a high conversion rate of acrylonitrile to polyacrylonitrile polymer, exceeding 97%, while maintaining the mechanical properties of the carbon fiber, thus reducing waste and costs associated with inefficient conversion.
Smart Images

Figure 0007625517000001 
Figure 0007625517000002 
Figure 0007625517000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 768,212, filed November 16, 2018, the entire contents of which are expressly incorporated herein by reference.
[0002] The present disclosure relates generally to the production of high conversion polyacrylonitrile-based polymers that can be incorporated into processes for producing carbon fibers, typically used in the production of composite materials. [Background technology]
[0003] Carbon fibers have been used in a wide variety of applications due to their desirable properties, such as high strength and stiffness, high chemical resistance, and low thermal expansion. For example, carbon fibers can be molded into structural parts that combine high strength and stiffness while weighing significantly less than metal components of comparable properties. Increasingly, carbon fibers are being used as structural components in composite materials, especially for aerospace and automotive applications. In particular, composite materials have been developed in which carbon fibers act as reinforcing materials in a resin or ceramic matrix.
[0004] Reducing costs and improving sustainability are desired goals of environmentally conscious carbon fiber and composite manufacturers. Acrylonitrile-derived carbon fibers are typically produced by a series of manufacturing processes or stages including polymerization, spinning, drawing and / or washing, oxidation, and carbonization. Polyacrylonitrile (PAN) polymer is currently the most widely used precursor of carbon fibers. During the polymerization stage, acrylonitrile (AN), optionally with one or more comonomers, is converted to PAN polymer. Insufficient conversion of acrylonitrile to PAN polymer is typically observed during the polymerization stage, resulting in unconverted acrylonitrile, which is typically not recycled, leading to a large amount of waste and associated costs. Not only is this a significant cost generator, but the incineration process also poses sustainability issues due to the amount of energy used to dispose of AN and wasted materials. It is clear that increased conversion is beneficial in large-scale polymerization processes. However, efforts to increase AN conversion during the production of PAN polymer without changing the properties of the resulting polymer and therefore the resulting carbon fiber have not been fully realized.
[0005] Thus, there is a continuing need for methods to produce PAN polymers at high conversions, particularly during the production of polymer fibers used to make carbon fibers and composite materials, to reduce the amount of unreacted AN without compromising the properties of the resulting polymer and carbon fibers. Summary of the Invention [Means for solving the problem]
[0006] This objective, as well as other objectives which will become apparent from the following detailed description, are met by the method of the present disclosure.
[0007] In a first aspect, the present disclosure relates to a method for producing a polyacrylonitrile-based polymer, the method comprising reacting acrylonitrile with at least one comonomer in the presence of a radical initiator in a liquid medium, the radical initiator being present in an amount of about 0.6% to about 1.8% by weight relative to the amount of acrylonitrile, and in the absence of a chain transfer agent, thereby producing a polyacrylonitrile-based polymer.
[0008] In a second aspect, the present disclosure relates to a method for producing carbon fibers, the method comprising: a) producing a polyacrylonitrile-based polymer according to one or more of the processes described herein; b) spinning the polymer solution containing the polyacrylonitrile-based polymer produced in step a) into a coagulation bath to produce a carbon fiber precursor fiber; c) drawing the carbon fiber precursor fiber through one or more drawing baths and washing baths, thereby forming a substantially solvent-free drawn carbon fiber precursor fiber; and d) oxidizing the drawn carbon fiber precursor fibers of step c) to form stabilized carbon fiber precursor fibers, and then carbonizing the stabilized carbon fiber precursor fibers, thereby producing carbon fibers; Includes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] As used herein, the terms "a," "an," or "the" mean "one or more" or "at least one," and can be used interchangeably, unless otherwise stated.
[0010] As used herein, the term "comprises" encompasses "consists essentially of" and "consists of." The term "comprising" encompasses "consisting essentially of" and "consisting of."
[0011] A first aspect of the present disclosure relates to a method for producing a polyacrylonitrile-based polymer, the method comprising reacting acrylonitrile with at least one comonomer in the presence of a radical initiator in a liquid medium, the radical initiator being present in an amount of about 0.6% to about 1.8% by weight relative to the amount of acrylonitrile, and in the absence of a chain transfer agent, thereby producing a polyacrylonitrile-based polymer.
[0012] The amount of acrylonitrile is not particularly limited, however, a suitable amount of acrylonitrile at the start of the reaction is about 12.0% by weight to about 25.0% by weight, typically about 19.1% by weight to about 20.4% by weight, based on the amount of the liquid medium.
[0013] The polyacrylonitrile-based polymer may further include repeat units derived from comonomers, such as, but not limited to, vinyl-based acids such as methacrylic acid (MAA), acrylic acid (AA), and itaconic acid (ITA); methacrylate (MA), ethyl acrylate (EA), butyl acrylate (BA), methyl methacrylate (MMA), ethyl methacrylate (EMA), propyl methacrylate, butyl methacrylate, β-hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, 2-ethylhexyl acrylate, isopropyl acetate, vinyl acetate (VA), and vinyl propionate. vinyl amides such as vinyl imidazole (VIM), acrylamide (AAm), and diacetone acrylamide (DAAm); vinyl halides such as allyl chloride, vinyl bromide, vinyl chloride, and vinylidene chloride; ammonium salts of vinyl compounds and sodium salts of sulfonic acids, such as sodium vinyl sulfonate, sodium p-styrene sulfonate (SSS), sodium methallyl sulfonate (SMS), and sodium 2-acrylamido-2-methylpropane sulfonate (SAMPS). In one embodiment, the comonomer is itaconic acid (ITA).
[0014] The comonomer ratio (the amount of one or more comonomers relative to the amount of acrylonitrile) is not particularly limited. However, a suitable comonomer ratio is 0-20%, typically 1-5%, more typically 1-3%.
[0015] The polymers can be made by any polymerization method known to those skilled in the art. Exemplary methods include, but are not limited to, solution polymerization, dispersion polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, and variations thereof.
[0016] One suitable method involves mixing acrylonitrile (AN) monomer and comonomer described herein in a solvent in which the polymer is soluble, thereby forming a solution. The solution is heated to a temperature above room temperature (i.e., above 25°C). After heating, an initiator is added to the solution to start the polymerization reaction. Once polymerization is complete, unreacted AN monomer is removed (e.g., by degassing under high vacuum) and the resulting PAN polymer solution is cooled. At this stage, the polymer is in solution or dope form.
[0017] Examples of suitable solvents include, but are not limited to, dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), ethylene carbonate (EC), zinc chloride (ZnCl2) / water, and sodium thiocyanate (NaSCN) / water.
[0018] In another suitable method, the acrylonitrile (AN) monomer and comonomer described herein can be polymerized in a medium in which the resulting polymer is poorly soluble or insoluble, typically an aqueous medium. In this method, the resulting polymer will form a heterogeneous mixture with the medium. The polymer is then filtered and dried.
[0019] Radical initiators can typically be divided into two general types depending on the manner in which the initial radical species is formed. The first type of radical initiator is activated by homolytic decomposition of a covalent bond by absorption of energy, typically heat. For the purposes of this specification, this type of radical initiator is considered a thermally activated radical initiator. The second type of radical initiator is activated by electron transfer from an ion or atom containing an unpaired electron, followed by dissociation of a bond in the acceptor molecule. For the purposes of this specification, this type of radical initiator is considered a redox radical initiator.
[0020] In one embodiment, the radical initiator comprises one or more thermally activated initiators. In such an embodiment, the polymerization reaction mixture does not contain a reducing agent. As used herein, the phrase "free of reducing agents" means that there is no exogenous addition of a material that can function as a reducing agent, and no detectable amount of the material that can be observed by analytical techniques known to those skilled in the art, such as, for example, gas or liquid chromatography, spectrophotometry, optical microscopy, etc. As used herein, a reducing agent refers to a compound that can donate one or more electrons to an acceptor molecule in a redox reaction involving the electron transfer required to activate a redox radical initiator. Examples of reducing agents that are not present in the polymerization reaction mixture include, but are not limited to, thiourea dioxide (also known as formamidine sulfinic acid), hydrazo-isobutyric acid, ascorbic acid and its derivatives, such as d-xyloascorbic acid, erythroascorbic acid, and araboscorbic acid, and their salts; formaldehyde sulfoxylate (SFS), tetramethylethylenediamine (TMEDA), and metabisulfite salts, such as sodium metabisulfite.
[0021] Thermally activated initiators (also called radical initiators or catalysts) suitable for polymerization include, but are not limited to, azo-bisisobutyronitrile (AIBN), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride ... azo compounds such as 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propane], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis-(2,4-dimethyl)valeronitrile (ABVN); and organic peroxides such as dilauroyl peroxide (LPO), di-tert-butyl peroxide (TBPO), diisopropyl peroxydicarbonate (IPP), among others.
[0022] The radical initiator is present in an amount of about 0.6% to about 1.8% by weight based on the amount of acrylonitrile. In one embodiment, the radical initiator is present in an amount of about 0.7% to about 1.4% by weight based on the amount of acrylonitrile, typically about 1.1% to about 1.3% by weight, and more typically about 1.2% to about 1.3% by weight.
[0023] In one embodiment, the radical initiator is present in an amount of at least 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, or 1.2% by weight and less than 1.8% by weight based on the amount of acrylonitrile. In another embodiment, the radical initiator is present in an amount of at least 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, or 1.2% by weight and less than 1.3% by weight based on the amount of acrylonitrile.
[0024] The reaction temperature is usually above room temperature (i.e., above 25° C.). Suitably, the reaction is maintained at a temperature of from about 30° C. to about 85° C., typically from about 40° C. to about 85° C., more typically from about 58° C. to about 72° C.
[0025] The method for producing polyacrylonitrile-based polymers described herein is carried out in the absence of chain transfer agents. As used herein, the phrase "absent chain transfer agents" means that there is no external addition of materials that can function as chain transfer agents, and that there is no detectable amount of material that can be observed by analytical techniques known to those skilled in the art, such as gas or liquid chromatography, spectrophotometry, optical microscopy, and the like. Exemplary compounds known to those skilled in the art to be chain transfer agents and that are not present in the methods described herein include, but are not limited to, carbon tetrachloride (CCl4), carbon tetrabromide (CBr3), bromotrichloromethane (BrCCl3), pentaphenylethane, compounds with one or more -SH functional groups (such as dodecyl mercaptan, also known as mercaptan or thiol), and compounds with one or more -(C=S)-S- and / or -SS- functional groups (such as the chain transfer agents disclosed in US Patent Publication No. 2015 / 0174807 to Longgui Tang et al.).
[0026] The conversion rate, which means the amount of acrylonitrile converted to polyacrylonitrile-based polymer relative to the total amount of acrylonitrile used at the beginning of the process, is unexpectedly high: the amount of acrylonitrile converted to polyacrylonitrile-based polymer relative to the total amount of acrylonitrile used is at least 97.0%, at least 97.1%, at least 97.5%, at least 97.7%, or at least 99.0%, and typically up to 99.5%.
[0027] Polyacrylonitrile-based polymers can be characterized by one or more properties, such as intrinsic viscosity, known to those skilled in the art. The intrinsic viscosity of polyacrylonitrile-based polymers produced according to the methods described herein ranges from about 1.3 to about 2.3, typically from about 1.7 to about 2.3, and more typically from about 1.7 to about 1.9.
[0028] In a second aspect, the present disclosure provides a method for producing a pharmaceutical composition comprising: a) producing a polyacrylonitrile-based polymer according to the process described herein; b) spinning the polymer solution containing the polyacrylonitrile-based polymer produced in step a) into a coagulation bath to produce a carbon fiber precursor fiber; c) drawing the carbon fiber precursor fiber through one or more drawing baths and washing baths, thereby forming a substantially solvent-free drawn carbon fiber precursor fiber; and d) oxidizing the drawn carbon fiber precursor fibers of step c) to form stabilized carbon fiber precursor fibers, and then carbonizing the stabilized carbon fiber precursor fibers, thereby producing carbon fibers; The present invention relates to a method for producing carbon fibers, comprising the steps of:
[0029] In step b) of the method, carbon fiber precursor fibers are formed by spinning a polymer solution comprising a polyacrylonitrile-based polymer into a coagulation bath. The term "precursor fiber" refers to a fiber comprising a polymer-based material that can be converted, upon application of sufficient heat, into a carbon fiber having a carbon content of about 90% by weight or more, in particular about 95% by weight.
[0030] If the polymer is formed in a medium in which it is soluble, typically one or more solvents, the resulting polymer solution can be spun directly in step b).If the polymer is formed in a medium in which it is poorly soluble or insoluble, typically an aqueous medium, the polymer can be isolated, for example by filtration, and then dissolved in one or more solvents to form a polymer solution suitable for use in step b).
[0031] After removing air bubbles by vacuum, the polymer solution (i.e., spin "dope") can be subjected to conventional wet spinning and / or air gap spinning. The spin dope can have a polymer concentration of at least 10% by weight, typically about 16% to about 28% by weight, and more typically about 19% to about 24% by weight, based on the total weight of the solution.
[0032] In wet spinning, the dope is filtered and extruded through holes in a spinneret (typically made of metal) into a liquid coagulation bath for the polymer to form filaments. The spinneret holes determine the desired filament count of the fiber (e.g., 3,000 holes for 3K carbon fiber).
[0033] In air-gap spinning, a vertical air gap of 1-50 mm, typically 2-10 mm, is provided between the spinneret and the coagulation bath. In this spinning process, the polymer solution is filtered and extruded in air through the spinneret, and the extruded filaments are then coagulated in a coagulation bath.
[0034] In one embodiment, the step of spinning the polymer solution into the coagulation bath comprises air gap spinning the polymer solution into the coagulation bath.
[0035] The coagulation liquid used in the present method is a mixture of a solvent and a non-solvent. Water or alcohol is typically used as the non-solvent. Suitable solvents include those described herein. In one embodiment, dimethylsulfoxide, dimethylformamide, dimethylacetamide, or a mixture thereof is used as the solvent. In another embodiment, dimethylsulfoxide is used as the solvent. The ratio of the solvent to the non-solvent and the bath temperature are not particularly limited and can be adjusted according to known methods to achieve a desired coagulation rate of the nascent filaments extruded in the coagulation. However, the coagulation bath typically contains 40% to 85% by weight of one or more solvents, the remainder being a non-solvent such as water or alcohol. In one embodiment, the coagulation bath contains 40% to 70% by weight of one or more solvents, the remainder being a non-solvent. In another embodiment, the coagulation bath contains 50% to 85% by weight of one or more solvents, the remainder being a non-solvent.
[0036] Typically, the temperature of the coagulation bath is between 0° C. and 80° C. In one embodiment, the temperature of the coagulation bath is between 30° C. and 80° C. In another embodiment, the temperature of the coagulation bath is between 0° C. and 20° C.
[0037] The drawing of the carbon fiber precursor fiber is performed by conveying the spun precursor fiber through one or more drawing baths and washing baths, for example by rollers. The carbon fiber precursor fiber is conveyed through one or more washing baths to remove excess solvent, and drawn in a hot (e.g., 40°C to 100°C) water bath to impart molecular orientation to the filaments as a first step in fiber diameter control. The result is a substantially solvent-free carbon fiber precursor fiber that is drawn.
[0038] In one embodiment, the carbon fiber precursor fibers are stretched by between -5% and 30%, typically between 1% and 10, and more typically between 3 and 8%.
[0039] Step c) of the method may further comprise drying the substantially solvent-free drawn carbon fiber precursor fibers, for example on drying rolls. The drying rolls may consist of a plurality of rotatable rolls arranged in series and in a serpentine configuration over which the filaments pass from roll to roll sequentially and under sufficient tension to provide drawing or relaxation to the filaments on the rolls. At least some of the rolls are heated by pressurized steam circulating therein or through the rolls, or by electric heating elements inside the rolls. A finishing oil may be applied onto the drawn fibers before drying to prevent the filaments from sticking to each other in downstream processes.
[0040] In step d) of the methods described herein, the drawn carbon fiber precursor fibers of step c) are oxidized to form stabilized carbon fiber precursor fibers, and the stabilized carbon fiber precursor fibers are subsequently carbonized to produce carbon fibers.
[0041] During the oxidation stage, the drawn carbon fiber precursor fibers, typically PAN fibers, are fed under tension through one or more specialized ovens, each having a temperature of 150-300°C, typically 200-280°C, more typically 220-270°C. Heated air is fed into each oven. Thus, in one embodiment, the oxidation of step d) is carried out in an air environment. The drawn carbon fiber precursor fibers are conveyed through one or more ovens at a speed of 4-100 fpm, typically 30-75 fpm, more typically 50-70 fpm.
[0042] During the oxidation process, oxygen molecules from the air combine with the fibers and initiate cross-linking of the polymer chains, which increases the fiber density to 1.3 g / cm 3 Up to 1.4g / cm 3 In the oxidation process, the tension applied to the fiber is to control the fiber to be stretched or shortened, usually with a draw ratio of 0.8-1.35, typically 1.0-1.2. When the draw ratio is 1, there is no drawing at all. And when the draw ratio is greater than 1, the applied tension causes the fiber to be stretched. Such oxidized PAN fiber has an inmeltable ladder-type aromatic molecular structure and is ready for carbonization.
[0043] Carbonization results in the crystallization of the carbon molecules, resulting in finished carbon fibers having a carbon content of greater than 90 percent. Carbonization of the oxidized or stabilized carbon fiber precursor fibers is carried out in an inert (oxygen-free) atmosphere in one or more specially designed furnaces. In one embodiment, the carbonization of step d) is carried out in a nitrogen environment. The oxidized carbon fiber precursor fibers are passed through one or more ovens, each heated to a temperature between 300°C and 1650°C, typically between 1100°C and 1450°C.
[0044] In one embodiment, the oxidized fibers are carbonized by passing through a pre-carbonization furnace exposed to a heating temperature of about 300°C to about 900°C, typically about 350°C to about 750°C, while exposed to an inert gas (e.g., nitrogen), followed by passing through a furnace heated to a higher temperature of about 700°C to about 1650°C, typically about 800°C to about 1450°C, while exposed to an inert gas. Tension on the fibers can be applied throughout the pre-carbonization and carbonization processes. In pre-carbonization, the fiber tension applied is sufficient to control the draw ratio to be in the range of 0.9 to 1.2, typically 1.0 to 1.15. In carbonization, the tension used is sufficient to provide a draw ratio of 0.9 to 1.05.
[0045] Adhesion between the matrix resin and the carbon fibers is an important criterion in carbon fiber reinforced polymer composites, so during the manufacture of carbon fibers, surface treatments can be performed after oxidation and carbonization to enhance this adhesion.
[0046] Surface treatment can include pulling the carbonized fibers through an electrolytic bath containing an electrolyte, such as ammonium bicarbonate or sodium hypochlorite. The chemicals in the electrolytic bath etch or roughen the surface of the fibers, thereby increasing the surface area available for interfacial fiber / matrix bonding and adding reactive chemical groups.
[0047] The carbon fibers can then be subjected to a sizing process in which a size coating (e.g., an epoxy-based coating) is applied onto the fibers. The sizing process can be carried out by passing the fibers through a size bath containing a liquid coating material. The sizing process protects the carbon fibers during handling and processing into intermediate forms, such as dry fabrics and prepregs. The sizing process also reduces fuzz, improves processability, and holds the filaments together in individual tows to increase the interfacial shear strength between the fiber and the matrix resin.
[0048] After sizing, the coated carbon fibers are dried and then wound onto a bobbin.
[0049] Those skilled in the art will appreciate that other processing conditions (such as spin solution and coagulation bath composition, total bath volume, drawing, temperature, and filament speed) are involved in order to obtain filaments of the desired structure and denier. The process of the present disclosure can be carried out continuously.
[0050] Carbon fibers produced according to the methods described herein can be characterized by mechanical properties such as tensile strength and tensile modulus according to ASTM D4018 test method.
[0051] The methods and materials of the disclosure are further illustrated by the following non-limiting examples. EXAMPLES
[0052] Example 1. A number of polymerization reactions were carried out in a 4 gallon reactor. Acrylonitrile (AN) was copolymerized with itaconic acid comonomer in dimethyl sulfoxide (DMSO) solvent in the presence of the radical initiator azo-bisisobutyronitrile (AIBN) and with or without the chain transfer agent dodecyl mercaptan (DM). The reactor temperature was controlled to maintain the polymerization reaction in the range of 58-72°C. The amounts of reagents used are summarized in Table 1 below.
[0053] TIFF0007625517000001.tif77170
[0054] Table 2 below summarizes the AN conversions of the polymers obtained in runs A-F.
[0055] TIFF0007625517000002.tif71170
[0056] It can be seen that high conversion (at least 97.0%) is achieved when a certain amount of radical initiator is used in the polymerization reaction in the absence of a chain transfer agent, as shown in Table 2. Although high conversion was observed in experiment C using a chain transfer agent, the resulting polymer exhibited low intrinsic viscosity and low solution viscosity, which was unsuitable for the production of carbon fibers.
[0057] A concern associated with increasing initiator concentration is the effects observed after polymerization. Typically, spinning experiments can take longer than 24 hours to consume an entire batch of polymerization material, which allows enough time for changes to occur in the spin dope. Surprisingly, however, the polymer solution was found to be stable at the dope spinning temperature (approximately 50-55 °C) for extended periods of time after polymerization.
[0058] Example 2. The polymerization reaction was carried out on a pilot scale using the same conditions as in Example 1, Run F, with the only change for the pilot test being that the reactor underwent a degassing cycle and an ammonia addition step. Ammonia addition was controlled from an ammonia cylinder at 20 psi and 86% SCFH flow meter. The AN conversion for this reaction is shown in Table 3 below.
[0059] TIFF0007625517000003.tif36170
[0060] Approximately 0.35% AN was detected remaining from the reaction. As shown in Table 3, the unreacted AN is in good agreement with the 97.6% conversion. This example shows that the process of the present invention to produce PAN polymer at high conversion without the need for chain transfer agents can be achieved even on a pilot scale without compromising polymer properties.
[0061] Example 3. PAN polymer made according to the process described in Example 2 was converted into carbon fiber.
[0062] The PAN polymer was subjected to a spinning process to produce precursor fibers. During spinning, there was no pressure build-up or filtration problem with the PAN polymer produced according to the process described in Example 2. The metering and booster pumps were stable during the spinning test, indicating molecular-scale uniformity as well as no observable gels on the macroscale.
[0063] The PAN precursor fibers obtained from eight batches of polymer produced according to the process of the present invention were stretched, oxidized, and carbonized to form carbon fibers. For comparison, the PAN precursor fibers obtained from eight batches of polymer produced by a process with an AN conversion of about 92% and a chain transfer agent were subjected to the same stretching, oxidation, and carbonization steps to form carbon fibers. The mechanical properties of the carbon fibers are summarized in Tables 4 (comparative) and 5 (inventive) below.
[0064] TIFF0007625517000004.tif68170
[0065] TIFF0007625517000005.tif71170
[0066] In all cases, across the set of eight inventive and eight comparative samples, each property average was controlled within the polymer batch. Furthermore, the property averages were all identical (within 2%) between the inventive and comparative polymer batches, thus demonstrating that high conversion rates (at least 97.0%) can be achieved without compromising the mechanical properties of the final carbon fibers produced therefrom.
Claims
1. A method for producing a polyacrylonitrile-based polymer, comprising: (i) mixing acrylonitrile with at least one comonomer and one or more solvents to form a solution; (ii) heating the solution to a temperature greater than 25° C.; and (iii) adding a radical initiator to the heated solution to initiate a polymerization reaction, thereby producing a polyacrylonitrile-based polymer; Including, the radical initiator in the heated solution in step (iii) is present in an amount of about 1.1% to about 1.8% by weight based on the amount of acrylonitrile; During the polymerization reaction, no chain transfer agent is present in the heated solution; the one or more solvents are selected from the group consisting of dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), ethylene carbonate (EC), zinc chloride (ZnCl 2 ) / water, and sodium thiocyanate (NaSCN) / water; and The method of claim 1, wherein the amount of acrylonitrile converted to polyacrylonitrile-based polymer relative to the total amount of acrylonitrile used is at least 97.0%.
2. 2. The process of claim 1, wherein the amount of acrylonitrile at the start of the reaction is from about 12.0% to about 25.0% by weight based on the amount of liquid medium.
3. 3. The method of claim 1 or 2, wherein the at least one comonomer is selected from the group consisting of vinyl-based acids, vinyl-based esters, vinyl amides, vinyl halides, ammonium salts of vinyl compounds, sodium salts of sulfonic acids, and mixtures thereof.
4. 4. The method of any one of claims 1 to 3, wherein the at least one comonomer is selected from the group consisting of methacrylic acid (MAA), acrylic acid (AA), itaconic acid (ITA), methacrylate (MA), ethyl acrylate (EA), butyl acrylate (BA), methyl methacrylate (MMA), ethyl methacrylate (EMA), propyl methacrylate, butyl methacrylate, β-hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, 2-ethylhexyl acrylate, isopropyl acetate, vinyl acetate (VA), vinyl propionate, vinyl imidazole (VIM), acrylamide (AAm), diacetone acrylamide (DAAm), allyl chloride, vinyl bromide, vinyl chloride, vinylidene chloride, sodium vinyl sulfonate, sodium p-styrene sulfonate (SSS), sodium methallyl sulfonate (SMS), sodium 2-acrylamido-2-methylpropane sulfonate (SAMPS), and mixtures thereof.
5. The method according to any one of claims 1 to 4, wherein the radical initiator is selected from the group consisting of azo-based compounds, organic peroxides, and mixtures thereof.
6. The radical initiator is selected from the group consisting of azo-bisisobutyronitrile (AIBN), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis[2- 6. The method of any one of claims 1 to 5, wherein the peroxy group is selected from the group consisting of methyl-N-(2-hydroxyethyl)propionamide, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis-(2,4-dimethyl)valeronitrile (ABVN), dilauroyl peroxide (LPO), di-tert-butyl peroxide (TBPO), diisopropyl peroxydicarbonate (IPP), and mixtures thereof.
7. The process of any one of claims 1 to 6, wherein the radical initiator is present in an amount of about 1.1% to about 1.3% by weight based on the amount of acrylonitrile.
8. The process of any one of claims 1 to 7, wherein the reaction is maintained at a temperature of from about 30°C to about 85°C.
9. The method according to any one of claims 1 to 8, wherein the amount of acrylonitrile converted into a polyacrylonitrile-based polymer relative to the total amount of acrylonitrile used is in the range of 97.0% to 99.5%.
10. The method according to any one of claims 1 to 9, wherein the intrinsic viscosity of the polyacrylonitrile-based polymer produced ranges from about 1.3 to about 2.
3.
11. a) producing a polyacrylonitrile-based polymer according to the method of any one of claims 1 to 10; b) spinning the polymer solution containing the polyacrylonitrile-based polymer produced in step a) into a coagulation bath to produce a carbon fiber precursor fiber; c) drawing the carbon fiber precursor fibers through one or more drawing baths and washing baths, thereby forming substantially solvent-free drawn carbon fiber precursor fibers; and d) oxidizing the drawn carbon fiber precursor fibers of step c) to form stabilized carbon fiber precursor fibers, and then carbonizing the stabilized carbon fiber precursor fibers, thereby producing carbon fibers; A method for producing carbon fibers, comprising:
Citation Information
Patent Citations
Acrylonitrile copolymer spinning solution with high molecular weight and narrow distribution and preparation method thereof
CN101805936A
A kind of preparation method of polyacrylonitrile resin with uniform distribution of copolymerization sequence
CN104371060B
Preparation method of hydrophilic low molecular weight distribution acrylonitrile copolymer spinning solution
CN106591994A
Preparation method for boron-containing polyacrylonitrile protofilament and carbon fiber thereof and graphite fiber
CN106917156A
A copolymer melt-spinnable from polyacrylonitrile, a method for producing fibers or fiber precursors using melt spinning, and fibers produced by said method
JP2017530231A